Pemahaman dan Penghayatan Makna Ekaristi bagi Orang Muda Katolik di Paroki Santa Ursula Watutumou - Fecky Evendy Singal; Jearne Felix Imbang (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2023)
ABSTRACT The purpose of this study is to describe the understanding of the Catholic Young People's group about the eucharist, the Catholic Youth's appreciation and the efforts that need to be made to increase the Catholic Young People's understanding and appreciation of the Eucharist. The type of research used is descriptive research with a qualitative approach. Data collection techniques were carried out in three ways, namely: Observation, Interview and Documentation Study. In this study, the research actors and informants were selected by the authors using a purposive procedure, namely the determination of informants by selecting key people who match the criteria and research problems. The conclusion of this study consists of three parts. First: Young Catholics in the Parish of Santa Ursula Watutumou already understand quite well about the Eucharist as the source and peak of the Christian faith, where in the Eucharist a direct encounter with God occurs through the event of transubstantiation. Second: OMK in Santa Ursula Watutumou Parish is able to appreciate the meaning of the Eucharist as an important celebration in the Church, so that because of the basis of the Eucharist itself, OMK seeks to realize the Eucharist as a necessity, not just a meaningless routine, and tries to be actively involved by increasing the role of the Eucharist. and OMK in the celebration of the Eucharist. Third: Efforts that can be made to increase understanding and appreciation of OMK in Santa Ursula Watutumou Parish, among others by participating in worship, diligently attending Sunday Mass and daily Mass and being actively involved in them, following the example of parents who provide examples and motivation in interpreting the Eucharist, and participating in faith deepening activities such as socialization and catechesis on the Eucharist.